Abdominal epilepsia partialis continua in neurocysticercosis. Issue 3 (17th July 2019) - Asranna, Ajay; Sureshbabu, Sachin; Mittal, Gaurav; Peter, Sudhir; Chindripu, Shobhana; Saini, Leena
ABSTRACT: Epilepsia partialis continua (EPC) of abdominal muscles is a rare entity with variable clinical localization and aetiology. A 25‐year‐old man presented with sudden onset of intermittent focal myoclonic movements involving the abdominal muscles on the right side exclusively, lasting from 20 minutes to an hour. Brain MRI revealed a ring‐enhancing lesion, suggestive of cysticercal granuloma over the left precentral gyrus. The patient fulfilled the revised diagnostic criteria for definitive diagnosis of neurocysticercosis. EEG did not show focal abnormalities during the events. Episodes of EPC were controlled with difficulty using 600 mg oxcarbazepine, 200 mg lacosamide, and 2, 000 mg levetiracetam. The patient received antiparasitic therapy with albendazole (15 mg/kg for two weeks) and oral dexamethasone (0.1 mg/kg) for two weeks which was then tapered. The involvement of the primary motor cortex during ictal propagation may account for this curious phenomenon. This is the first report of abdominal EPC in a patient with inflammatory granuloma as a result of neurocysticercosis.